On Certain Matrices of Bernoulli Numbers - Zhang, Ruiming; Chen, Li-Chen (Abstract and Applied Analysis, 2014)
In this work we compute the determinant and inverse matrices for a certain symmetric matrix of Rayleigh sums. As a special case we also obtain the determinants and inverses for the matrices of the Bernoulli numbers and related numbers.